Gut microbiota and oleoylethanolamide in the regulation of intestinal homeostasis - De Filippo, Carlotta; Costa, Alessia; Becagli, Maria Vittoria; Monroy, Mariela Mejia; Provensi, Gustavo; Passani, Maria Beatrice (Frontiers in Endocrinology, 2023)
A vast literature strongly suggests that the endocannabinoid (eCB) system and related bioactive lipids (the paracannabinoid system) contribute to numerous physiological processes and are involved in pathological conditions such as obesity, type 2 diabetes, and intestinal inflammation. The gut paracannabinoid system exerts a prominent role in gut physiology as it affects motility, permeability, and inflammatory responses. Another important player in the regulation of host metabolism is the intestinal microbiota, as microorganisms are indispensable to protect the intestine against exogenous pathogens and potentially harmful resident microorganisms. In turn, the composition of the microbiota is regulated by intestinal immune responses. The intestinal microbial community plays a fundamental role in the development of the innate immune system and is essential in shaping adaptive immunity. The active interplay between microbiota and paracannabinoids is beginning to appear as potent regulatory system of the gastrointestinal homeostasis. In this context, oleoylethanolamide (OEA), a key component of the physiological systems involved in the regulation of dietary fat consumption, energy homeostasis, intestinal motility, and a key factor in modulating eating behaviour, is a less studied lipid mediator. In the small intestine namely duodenum and jejunum, levels of OEA change according to the nutrient status as they decrease during food deprivation and increase upon refeeding. Recently, we and others showed that OEA treatment in rodents protects against inflammatory events and changes the intestinal microbiota composition. In this review, we briefly define the role of OEA and of the gut microbiota in intestinal homeostasis and recapitulate recent findings suggesting an interplay between OEA and the intestinal microorganisms.